STUDY REVIEW OF DENGUE FEVER – CLINICAL AND LABORATORY PARAMETERS ASSOCIATED WITH COMPLICATIONS - Mazen Mohammed Ahmad Al Ghamdi; Abdullatif Dakhilallah Alharthi; Saad Tayir Saeed Alahmari; Eman Fulayyih Alaswad Alanazi; Rana Mohammad Hassan; Fayez Abdulrahman Alhindi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Dengue fever is a mosquito-b viral disease that poses a significant public health concern in many tropical and subtropical regions. This study aims to review the clinical and laboratory parameters associated with complications of dengue fever. A comprehensive search was conducted using reputable databases for relevant articles published in reputed journals. Ten articles were selected based on their relevance, methodology, and scientific rigor. The articles provided insights into the clinical and laboratory features associated with severe dengue and its complications.